IODINE LEVEL OF IODIZED SALT REQUIRED IN ENDEMIC AREA - Gunung, I Komang (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 2, No. 2 Mei 2008)
Iodized salt had been used in many countries for long term iodine deficiency disorders (IDD) control program. Several things should be considered related to iodine loss in iodized salt, e.g. iodine loss during cooking that may effect the effectivity of the program. Too high iodine level on the other hand, will cause health problems such as iodine-induced hyperthyroidism (IIH) and autoimmune thyroiditis. The purpose of this study was to know the level of iodine in iodized salt required in endemic area to meet the iodine recommended daily allowance (RDA) of 150 ?g/person/day. This study was a field trials using treatment by subyect design. Ten schoolchildren were selected systematically to get ten clusters of schoolchildren families. All members of the families were 33 persons (2 families were droped out). Urine examination showed the mean of urine iodine excretion (UIE) 84.8 ± 32.11 ?g/L and 208.1 ± 89.24 ?g/L of non-iodized salt and iodized salt consumption respectively. Salt intake was 6.64 g/person/day and iodine loss during cooking was 25%. Iodine level of iodized salt required in mild endemic area was 22 ppm at consumer level or 32 ppm at production level. This result was slightly higher than the minimum range (30 ppm) and much lower than the maximum range (80 ppm) was the level of iodine in iodized salt that was detemined by the government (30-80 ppm). Based on this finding, the range of iodine level in iodized salt production should be rivised according to the endemicity of area (mild, moderate, and severe).
Keywords: iodized salt, iodine loss, UIE, salt intake